The Politics of Change
VII, 212 p.
Keywords: This work takes a critical view of the debate on globalization and assesses revamped versions of structuralist thought, which underpin much of the globalization discourse. In contrast to conventional views of change, the book emphasizes change as a politics of emancipation.